Efficacy of Percutaneous Endoscopic Lumbar Foraminotomy in Treating Foraminal Stenosis: A Prospective Study - Rehman, Yaqoob Ur; Uddin, Afaq; Muhammad, Riaz; Ali Safi, Akbar (Journal of Neonatal Surgery, 2025)
Background: Foraminal stenosis is a disorder in which the opining of the spine (neural foramina) becomes narrow and compresses the nerves that leave the spinal cord. The regions supplied by the affected nerves may experience pain, tingling, numbness, or weakness as a result of this constriction. So early treatment is crucial in this case. One of the effective approaches to treat lumbar foraminal stenosis is PELF. Objective: The aim of this study was to find out the efficacy of Percutaneous Endoscopic Lumbar Foraminotomy in Treating Foraminal Stenosis Material and methods: The current Prospective Study was carried out at the orthopaedic department, Nowshera Medical College and Qazi Hussain Ahmad Medical Complex Nowshera. The study duration was six months from January 2024 to June 2024 after taking approval from the ethical committee of the hospital. A total of 37 individuals with lumber stenosis who had performed Percutaneous Endoscopic Lumbar foraminotomy were enrolled in this study. Chart reviews, patient-based outcome questionnaires, and phone interviews were used to collect data. The visual analogue scale (VAS) score was used to measure the individuals' degrees of radicular leg pain and back pain. The Oswestry Disability Index was used to evaluate functional status. The modified MacNab criteria were also used for assessing the clinical results. A paired t test with the Bonferroni approach for multiple comparison correction and repeated-measures analysis of variance were used to compare the clinical outcomes in pain and functional status before and after surgery. P-values of.05 were considered significant. Results: A total of 37 individuals were included in this study out of which 20 were females and 17 were males. The mean age of the study participants was 65.3 years with a range of 17 to 81 years. For back pain, the mean before surgery VAS score were SD = 2.05. At six weeks, six months, 1 year, & 2 years after surgery, this score improved to SD = 1.77 (P value less than 0.001). Preoperative leg pain had a mean VAS score of SD = 1.33. At six weeks, 6 months, one year, & two years after surgery, this score improved (P value less than 0.001). At six weeks, six months, one year, and two years after surgery, the mean postoperative ODI score were improved. The modified MacNab criteria were graded as follows at the final follow-up review: 31.8% had an excellent rating, 40.5% had a good, 32.4% had a fair, and 5.4% had a poor score. Consequently, 81.0% had excellent or good outcomes, and 35 out of 37 participants (94.5%) had an improvement in their symptoms. Conclusion: The present study concluded that percutaneous endoscopic lumbar foraminotomy in treating foraminal Stenosis is very effective and this surgical procedure has grown more standardized and useful